The rhetorical tradition in Philosophical Hermeneutics - ahmad ali heidari (حکمت و فلسفه, 2017)
Hermeneutics has a close relationship with the rhetorical tradition. From the time of Plato and the genesis of philosophical thought, emphasis was put on the distinction and independence of syllogism and rhetoric. However, thanks to Aristotle's meditations on the relation between these approaches, the way was paved for similarities between the two fields. Philosophical hermeneutics in the 20th century, with an eye to the importance of rhetoric for human understanding and its relation with the life-world of humans, intends to include rhetoric using the concept of authenticity in Heidegger, the ubiquity of the element of understanding in Gadamer or Riceour's theory of metaphor and show both the identical aspects and the conflicting connection between hermeneutics and rhetoric; though it has doubts regarding the acceptance of the effects of this partial independence.